Energy balance, greenhouse gas emissions, and profitability of thermobarical pretreatment of cattle waste in anaerobic digestion. (March 2016) - Budde, Jörn; Prochnow, Annette; Plöchl, Matthias; Suárez Quiñones, Teresa; Heiermann, Monika
Highlights: Theoretical integration of a model device for thermobarical treatment in a biogas plant. Thermobarical pretreatment is beneficial for raw material with high contents of organic dry matter and ligno-cellulose. The additional benefits exceed the additional expenses in terms of energy, greenhouse gas emissions, and profitability. Solid cattle waste revealed very short payback times for greenhouse gases and economic amortization. Liquid cattle waste if used as replacement does not show additional positive effects. Abstract: In this study modeled full scale application of thermobarical hydrolysis of less degradable feedstock for biomethanation was assessed in terms of energy balance, greenhouse gas emissions, and economy. Data were provided whether the substitution of maize silage as feedstock for biogas production by pretreated cattle wastes is beneficial in full-scale application or not. A model device for thermobarical treatment has been suggested for and theoretically integrated in a biogas plant. The assessment considered the replacement of maize silage as feedstock with liquid and/or solid cattle waste (feces, litter, and feed residues from animal husbandry of high-performance dairy cattle, dry cows, and heifers). The integration of thermobarical pretreatment is beneficial for raw material with high contents of organic dry matter and ligno-cellulose: Solid cattle waste revealed very short payback times, e.g. 9 months for energy, 3 months for greenhouse gases, and 3 years 3 months for economic amortization, whereas, in contrast, liquid cattle waste did not perform positive replacement effects in this analysis.